Research Achievements of Hot Pepper (Capsicum Species) and it Agro-Ecological Requirements in Ethiopia a Review - Gebresilassie, Nigussie; Israel, Zewdia (Journal of Farming, 2023)
Hot pepper is an important spice and vegetable crop in Ethiopia. Its production is constrained by a number of problems among which climatic condition is the primary. The amount rain fail temperature humidity the solanaceous groups of vegetables including hot pepper generally are sensitive to environmental conditions. The amount of rain fall required depends on the altitude of the environment, wind speed sunshine hour, which in turn is influenced by a number of genetic and environmental variables. In the absence of any other production constraints, suitable climatic condition and yield of hot pepper are closely related. Pepper, like other crop produces well when it is grown in good environmental condition. Farmers produce hot pepper in different environment without considering the suitable environment. The yield of hot pepper varies year to year; this indicates that pepper crop need intensive care and management for high return per unit area and also appropriate environmental condition. So in order to produce good hot pepper with the required amount of capsaicinoid content it is butter to grow at temperature range of 17.5-28oc. at low altitude hot environment give high capsaicinoid content and in high altitude / Low humidity and high temperatures will cause abscission of buds, flowers and small fruits.
Keywords: Altitude; capsaicinoid; climatic condition; gentic variable; hot pepper